Pengaruh Sertifikasi Dan Label Halal Terhadap Persepsi Kualitas Produk Makanan Di Kabupaten Sumbawa - Irawan, Feri (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The purpose of this study is to analyze the impact of halal certification and labeling on the perceived quality of food products in Sumbawa Regency. The research method used is a quantitative approach with survey techniques, where data is collected through questionnaires from 400 respondents spread across various markets and shopping centers. The results of multiple linear regression analysis show that halal certification and labeling have a significant effect on the perceived quality of food products. Halal certification is more influential (regression coefficient 0.456) than halal labeling (regression coefficient 0.389). This suggests that consumers tend to have more confidence in halal certification as a more in-depth quality assurance. The halal label, while serving as an important visual marker, does not provide the same quality assurance in the absence of formal certification. These findings suggest that manufacturers need to pay attention to the importance of obtaining legitimate halal certification to increase consumer confidence. In addition, the government and certification bodies should increase supervision of products in circulation with halal labels to ensure authenticity and compliance with halal standards. This research provides important information for manufacturers, consumers, and policy makers to support the growth of the halal industry.